Comparison of N-doped carbon dots synthesized from the main components of plants including cellulose, lignin, and xylose: Characterized, fluorescence mechanism, and potential applications. (December 2020) - Liao, Xiufen; Chen, Congjin; Zhou, Ruxia; Huang, Quanlong; Liang, Qinglong; Huang, Zuqiang; Zhang, Yanjuan; Hu, Huayu; Liang, Yanglin
Abstract: In this study, N-doped carbon dots (N-CDs) synthesized from the main components of plants, including cellulose (N-cCDs), lignin (N-lCDs), and xylose (N-xCDs), were compared. TEM, XRD, FT-IR, and XPS were carried out to characterize their morphology and chemical composition. Results show that the three obtained N-CDs contained N-doped sp 2 and sp 3 hybrid carbon core, which was surrounded by oxygen- and nitrogen-containing functional groups. The three N-CDs exhibited a novel double excitation-one emission phenomenon, and their fluorescence were significantly enhanced by N-doping. Moreover, this study indicated that high lignin-containing biomass is not appropriate for producing CDs by hydrothermal method. Cellulose is conducive to produce CDs, while it needs a relatively high temperature and a long time. Low-molecular carbohydrate-rich biomass and nitrogen-containing biomass is the better carbon source to produce the CDs. Also, this study revealed that N-cCDs and N-xCDs are excellent candidates for fluorescent ink, fabrics identifying, temperature sensing, and Hg 2+ sensing. Due to its poor fluorescence property, N-lCDs is not suitable for fluorescent ink and fabrics identification. Graphical abstract: Image 1 Highlights: ∙ N-CDs produced from the main components of plants have been compared. ∙Double excitation-one emission phenomenon for all of the CDs and N-CDs was discussed. ∙Fluorescence mechanism for the three CDs and N-CDs have been discussed. ∙Potential applications of the three N-CDs were studied.